The digital currency challenge : shaping online payment systems through US financial regulations - Mullan, P. Carl.; SpringerLink (Online service). (New York : Palgrave Macmillan US, 2014)
Details how new US legal issues surrounding digital currency products forced companies from the US market and caused the Treasury Department to enact stricter regulations.
Keywords: Science